Fracture resistance of in-situ healed CFRP composite using thermoplastic healants. (September 2020) - Jony, Bodiuzzaman; Roy, Samit; Mulani, Sameer B.
Abstract: In this study, macro fiber composite (MFC) assisted in-situ healing of unidirectional fiber reinforced polymer (FRP) composite was investigated and characterized by the double cantilever beam (DCB) tests. Biomimetic healing of delamination damage in carbon fiber reinforced composite (CFRP) was achieved by using a blend of biphasic healant: polycaprolactone (PCL) and polyurethane shape memory polymer (SMP). When the damage initiated at the fiber matrix interface or through the matrix, the thermoplastic SMP/PCL blend closed the crack due to localized stimulus (heat) provided by MFC. Crack closure was followed by healing via PCL healant using the same stimulus. Protocol for characterizing the healing efficiency of CFRP composite was established. The experimental results demonstrated that the localized healing method not only enables the in situ healing but also outperforms conventional healing methods in terms of healing efficiency. The MFC actuated healing yielded up to ∼160 % recovery of virgin interlaminar fracture property and ∼70 % flexure property recovery for seven healing cycles. This novel healing system can thus provide efficient in-situ healing in aerospace structures using MFC sensors as self-healing actuators, and bridge the gap between the laboratory scale and large-scale industrial application of self-healing polymer composite.